Оценка индивидуального ресурса литых корпусов автоматических защитных клапанов энергоблоков мощностью 200 МВт - Черноусенко, Ольга Юрьевна; Рындюк, Дмитрий Викторович; Пешко, Виталий Анатольевич; Горяженко, Владислав Юрьевич (НТУ "ХПИ", 2018)
Энергоблоки ДТЭК "Кураховская ТЭС" мощностью 200 МВт с паровыми турбинами К-200-130 после достижения ими паркового ресурса на сегодняшний день требуют принятия решения о дальнейшей эксплуатации. Данная работа посвящена проблеме продление срока эксплуатации энергетического оборудования. Предметом исследования работы является повреждаемость и остаточный ресурс автоматических защитных клапанов ЦСД паровой турбины К-200-130. Получены данные по тепловому и напряженно-деформированному состоянию корпусов клапанов для разных режимов пуска. Определена суммарная поврежденность и индивидуальный остаточный ресурс.

Most Ukrainian heat power plants have already worked off their fleet life according to the current normative documents. However, previous investigations of the physical-&-mechanical structure of metal used for the cast body parts of steam turbines show that there is an opportunity for the recurring extension of the service life of this equipment. Since cast high-temperature casings are one of the most expensive elements of the steam turbine, an issue of the possibility of refreshing extension of their service life remains to be a problem of strategic importance. Using as an example the power-generating units of "Kurakhovskaia Heat Power Plant" of 200 MW with steam turbines K-200-130 the residual resource of high-temperature elements of the power equipment, in particular the self-actuating safety valve (SSV) of an average pressure cylinder (APC) has been estimated. This scientific paper gives computation data of thermal elastically deformed state of the casings of self-actuating safety valves of the APC taking into account a joint action of the temperature gradient and internal steam pressure in-operation. Availability of service damages in the design structure and the results of repair and restoration changes were taken into account. A total damageability of the casing metal of SSV of the average pressure cylinder was determined based on the computation in terms of low-cycle fatigue and static damageability. The recommendations on the possibility of the refreshing extension of their service life were given.
Estimating an individual life of the cast casings of self-acting safety-valves of the power generating units of 200 MW
Keywords: холодное состояние; неостывшее состояние; горячее состояние; остаточный ресурс; малоцикловая усталость; длительная прочность; residual life